2018
DOI: 10.1017/s0714980818000211
|View full text |Cite
|
Sign up to set email alerts
|

Enoch Senior’s College for Korean Immigrant Seniors: Quality of Life Effects

Abstract: A community-based program is increasingly recognized as promoting health and active social participation in one's life, yet information is lacking about the use and impact of such programs among immigrant visible minority seniors. This mixed-method research evaluated the impact of a cultural community program for Korean immigrant seniors by examining participants' health-related quality of life (HR-QOL) benefits and overall well-being. In this study, 79 participants completed the SF-36v2 questionnaire twice to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 72 publications
2
21
0
Order By: Relevance
“…This research aligns with the small number of other studies conducted with migrant populations in Australia and internationally. Other studies have highlighted the importance of independence [ 18 , 19 ] and social connections [ 20 , 21 ] to older adults from CALD backgrounds. The quality-of-life dimension of having a meaningful role identified in a previous study [ 18 ] was similar to the dimension of ‘purpose and meaning’ identified in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This research aligns with the small number of other studies conducted with migrant populations in Australia and internationally. Other studies have highlighted the importance of independence [ 18 , 19 ] and social connections [ 20 , 21 ] to older adults from CALD backgrounds. The quality-of-life dimension of having a meaningful role identified in a previous study [ 18 ] was similar to the dimension of ‘purpose and meaning’ identified in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of older Chinese adults in New Zealand identified the importance of maintaining independence and having strong family support [ 19 ]. Several studies have highlighted the importance of social connections with their ethnic community as important to older CALD adults, such as studies with older Punjabi women and older Korean adults in Canada [ 20 , 21 ]. Jo and colleagues [ 21 ] identified that having a sense of belonging and feeling valued were important to older Korean adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic proportion of older adults aged 55 to 65, has surpassed those aged 15 to 24 years of age (Statistics Canada, 2018b). In combination with the increase in the aging population, Canada’s demographic landscape is also changing due to a significant increase in ethnocultural diversity (Jo et al., 2018). According to the Statistics Canada 2016 census, there are 7.5 million immigrants which represents more than 1 in 5 persons in the Canadian population (Statistics Canada, 2018a).…”
Section: Background and Purposementioning
confidence: 99%
“…With an increasing aging population, there will be significant implications for all sectors of society, including labour, financial markets and the demand for goods and services (e.g., housing, transportation, and social protection) (United Nations, 2017). In conjunction with the increase in the aging population, the Canadian demographic landscape is changing due to a significant increase in ethnographic diversity (Jo, Jo, Veblen & Potter, 2018). According to the Statistics Canada 2016 census, immigrants accounted for more than 7.5 million, representing more than 1 in 5 persons in the Canadian population (Statistics Canada, 2018).…”
Section: Introductionmentioning
confidence: 99%